Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions.

I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your **free** account and access **expert** answers to this and **thousands** of other questions

You know that y=2-x, so plug in 2-x instead of y in the second equation and solve.

Hold on, lemme try

What's (2-x)^2?
Is it the long answer or like, the one with 2 numbers?

can't do it man, help me out here

If y = 2-x, then x = 2-y. Replace each x with 2-y

where do I go from 2-2y=5-3y^2?

English man, English

Rearrange the equation so that it is equal to 0. Make the y^2 term positive.

Also, it should be 4-2y not 2-2y

Oh

Actually, Mertsj is right, it's easier to replace x other than y.

Eh?

could one of you dudes just give me the answer +solution? It's REALLY late

\[(2-y)(2-y+y)=5-3y^2\]
\[(2-y)(2)=5-3y^2\]
\[4-2y=5-3y^2\]
\[3y^2-2y-1=0\]
\[(3y+1)(y-1)=0\]

Can you solve that for y?

waaaait

how did 3y^2-2y-1=0 become (3y+1)(y-1)=0
?

By factoring.

what method?

You can also use discriminant if you want.

Too many cooks.

mmm, well

thanks dudes, I'll try to figure this dang thing out

Sorry Helper
Can't give more than one medal